Pengaruh Kualitas Pelayanan, Akuntabilitas,Dan Religiusitas Terhadap Loyalitas Muzakki Dengan Kepercayaan Sebagai Variabel Intervening Di Lembaga Amil Zakat Kota Magelang (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
The purpose of this study was to examine and determine the effect of service quality, accountability and religiosity on muzakki loyalty with trust as an intervening variable at the Amil Zakat Institution in Magelang City. The method used in this research is a quantitative method with primary data, namely by collecting questionnaires (questionnaires). With a convenience sampling technique with a number of 100 respondents became the sample in this study. Furthermore, SPSS 25 application is used for data processing. Simultaneously service quality, accountability and religiosi have a positive and significant effect on muzakki loyalty. The results showed that partially service quality had a significant effect on muzakki loyalty. Accountability has no significant effect on muzakki loyalty. Religiosity has a significant effect on muzakki loyalty. Service quality has no effect on muzakki loyalty with trust as an intervening variable. Accountability has a significant effect on muzakki loyalty with trust as an intervening variable. Religiosity has no significant effect on muzakki loyalty with trust as an intervening variable.